Microstructural characterisation of a nickel alloy processed via blown powder direct laser deposition (DLD). (5th March 2017) - Jones, Jonathan; Whittaker, Mark; Buckingham, Ross; Johnston, Richard; Bache, Martin; Clark, Daniel
Abstract: A three dimensional structure of varying wall thickness has been manufactured from an alloy similar to 718 and subjected to metallographic characterisation. The technique is evaluated as a process capable of generating complex geometries. This can be used to add features or as a free form fabrication method. However, in order to allow for comparison to structures developed through more traditional techniques, detailed microstructural characterisation has been undertaken to attempt to understand the potential effect of variation on resultant mechanical properties. Samples were extracted from six locations with different wall thicknesses, intricate features and intersecting ligament geometry. A γ″ linearly arrayed structure within a γ matrix was consistent throughout the component. Micro-porosity was restricted to isolated, spherical pores < 1 μm in diameter. Electron back-scatter diffraction and X-ray computed microtomography quantitative microstructural analysis techniques have been utilized to assess the influence of layering upon microporosity, patternation and grain structure. A detailed comparison is also made between blown powder Direct Layer Deposition (DLD) and a similar deposition technique, shaped metal deposition (SMD). Blown powder DLD produces a smaller weld pool and results in a more consistent microstructure than SMD, with less evidence of unfavourable phases brought about by prolonged exposure to high temperatures. The improved microstructure, however, must be measured against the different process economics of the blown powder DLD technique. Graphical abstract: Highlights: The novel manufacturing technique has proved capable of providing a consistent microstructure in a complex geometry. The blown powder DLD component showed low porosity, although isolated spherical micro-pores were found widely distributed. Microstructural consistency indicates that these techniques are applicable for appropriate structural geometries. Despite a high capital cost, flexibility is ensured favouring high performance additive manufacturing applications.